Prognostic value of type 2 diabetes mellitus and visfatin level in patients after coronary artery bypass grafting - Alla A. Garganeeva; Elena A. Kuzheleva; Olga V. Tukish; Sergey L. Andreev; Oksana N. Ogurkova; Sergey V. Popov (Russian Open Medical Journal)
Objective — Our study aimed to evaluate the prognostic value of type 2 diabetes mellitus (DM) and the level of visfatin in patients undergoing coronary artery bypass grafting (CABG). Methods — Our study included 103 patients with chronic heart failure and stable coronary artery disease. The clinical outcomes and adverse cardiovascular events were analyzed 12 months after the CABG. Results — The patients were distributed between two groups: Group 1 (without registration of composite endpoints, n=71) and Group 2 (patients with the development of composite endpoints, n=32). In Group 1, 22.5% of patients were diagnosed with DM vs. 31.2% in Group 2 (p=0.346). Kaplan-Meier estimator demonstrated that patients with duration of DM over 5 years experienced significantly earlier and more frequent adverse cardiovascular events after CABG vs. patients without DM or with duration of DM less than 5 years. The visfatin level before CABG did not differ between the groups (p=0.416), whereas 10 days after CABG it was higher in Group 2. Correlation between the difference in visfatin levels before and after CABG and duration of type 2 DM was calculated (r=0.54, p=0.041). Conclusion — In patients after CABG, the duration of DM had a negative impact on the development of cardiovascular events. With a duration of DM exceeding 5 years, the risk of adverse events increased significantly. An increase in visfatin level 10 days after CABG was associated with the duration of DM and the development of adverse cardiovascular events in patients.